Frontal Horn Cysts in Normal Neonates - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Among 3545 term or near term healthy neonates who underwent cranial ultrasound over a 2-year 5-month period at Mackay Memorial Hospital, Taipei, Taiwan, 18 (0.5%) were diagnosed with frontal horn cysts (FHCs).